"I don't want to be a patient": Peer mentoring partnership fosters communication for autistic university students. (16th November 2020) - Thompson, C.; McDonald, J.; Kidd, T.; Falkmer, T.; Bölte, S.; Girdler, S.
Abstract: Background: Despite recognition of the benefits of post-school education in improving life outcomes for autistic adults their university completion rates remain low. Aim: To explore the experiences of undergraduate autistic university students participating in specialist peer mentoring (SPM) to identify active ingredients in the peer mentoring process and to examine the impact of SPM on social communication. Material and method: A total of 30 (8 female; M age = 22.3; SD = 6.7) undergraduate autistic university students engaged in SPM participated in this study. A quantitative pre-test post-test design examined changes in autistic traits. In parallel, the experiences of participating in SPM were explored through semi-structured interviews. Results: Improvements were noted at post-test on the Social Responsiveness Scale-2 total score p = 0.02), and its Social Communication, ( p = 0.03) and Social Motivation ( p = 0.03) sub-scales. Four themes emerged from the interviews: Developing Partnership and Understanding, Modelling and Practising Communication, Psychological Support and Grading and Planning Skills . Conclusions: These results indicated that the mentor-mentee partnership was a crucial active ingredient of SPM. This partnership appeared to modify social cognition and motivation for autistic university students through modelling and practising communication. Significance: These results demonstrate that SPM can support participation at university for autistic university students.